The Role of Preschool in Using Gadgets for Digital Natives Generation - N, Zulkifli; Novianti, Ria; Garzia, Meyke (Program Studi Magister Pendidikan Anak Usia Dini, 2021)
Digital natives’ generation is inseparable from gadgets, less socializing, lack of creativity and being an individualist. The digital native’s generation wants things that are instant and lack respect for the process. The preoccupation of children with gadgets makes children socially alienated or known as anti-social. Preschool play an important role in the development of the digital native’s generation and in the future can help children use gadgets with parents. As it is known, the digital native’s generation is a kindergarten child. This study aims to determine the role of preschools in helping the use of gadgets in the digital native generation. This study used a descriptive quantitative approach with simple random sampling technique was obtained 25 kindergarten principals in Pekanbaru City. Data was collected in the form of a questionnaire via google form. Data analysis uses percentages and is presented in the tabular form. The results of the study indicate that the role of preschools in the use of gadgets in digital native generation children in Pekanbaru City is included in the low category. Only a few preschools have organized parenting education for parents. There are almost no rules governing children's use of gadgets at home, and few preschools educate children on how to use gadgets properly. It is expected for teachers and preschools to add special programs in the curriculum to provide information about positive gadget use and parenting programs that discuss digital native generation and collaborate with parents to establish rules such as frequency, duration and content of children using gadgets. Keywords: Digital Native, Preschool, Gadgets References: Alia, T., & Irwansyah, I. (2018). Pendampingan orang tua pada anak usia dini dalam penggunaan teknologi digital [parent mentoring of young children in the use of digital technology]. Polyglot: Jurnal Ilmiah, 14(1), 65–78. Allen, K. A., Ryan, T., Gray, D. L., McInerney, D. M., & Waters, L. (2014). Social Media Use and Social Connectedness in Adolescents: The Positives and the Potential Pitfalls. The Australian Educational and Developmental Psychologist, 31(1), 18–31. https://doi.org/10.1017/edp.2014.2 Berlin, A., Törnkvist, L., & Barimani, M. (2016). Content and Presentation of Content in Parental Education Groups in Sweden. The Journal of Perinatal Education, 25(2), 87–96. https://doi.org/10.1891/1058-1243.25.2.87 Chapman, G., & Pellicane, A. (2014). Growing up social: Raising relational kids in a screen-driven world. Moody Publishers. Cho, K.-S., & Lee, J.-M. (2017). Influence of Smartphone Addiction Proneness of Young Children on Problematic Behaviors and Emotional Intelligence. Comput. Hum. Behav., 66(C), 303–311. https://doi.org/10.1016/j.chb.2016.09.063 Coie, J. D., & Dodge, K. A. (1988). Multiple sources of data on social behavior and social status in the school: A cross-age comparison. Child Development, 815–829. Crouch, A. (2017). Tech-Wise Family. Everyday Steps for Putting Technology in Its Proper Place. Baker Books. De Lima, L., & Castronuevo, E. (2016). Perception of parents on children’s use of gadgets. The Bedan Journal of Psychology, II, 26–34. Gani, S. A. (2017). Parenting Digital Natives: Cognitive, Emotional, and Social Developmental Challenges. Guralnick, M. J. (1999). Family and child influences on the peer‐related social competence of young children with developmental delays. Mental Retardation and Developmental Disabilities Research Reviews, 5(1), 21–29. Hosokawa, R., & Katsura, T. (2018). Association between mobile technology use and child adjustment in early elementary school age. PloS One, 13(7), e0199959. Jonathan, L. P., & Andrew, L. F. (2016). Depression in children and adolescents. University of Kansas, Clinical Child Psychology Program. Kabali, H. K., Irigoyen, M. M., Nunez-Davis, R., Budacki, J. G., Mohanty, S. H., Leister, K. P., & Bonner, R. L. (2015). Exposure and Use of Mobile Media Devices by Young Children. PEDIATRICS, 136(6), 1044–1050. https://doi.org/10.1542/peds.2015-2151 Kirschner, P. A., & De Bruyckere, P. (2017). The myths of the digital native and the multitasker. Teaching and Teacher Education, 67, 135–142. https://doi.org/10.1016/j.tate.2017.06.001 Kurniawan, A. R., Chan, F., Sargandi, M., Yolanda, S., Karomah, R., Setianingtyas, W., & Irani, S. (2019). Kebijakan Sekolah Dalam Penggunaan Gadget di Sekolah Dasar [School Policy on the Use of Gadgets in Elementary Schools]. Jurnal Tunas Pendidikan, 2(1), 72–81. Martin, D. J. (2001). Constructing Early Childhood Science. Delmar Thomson Learning, Inc,. Morrongiello, B. A., McArthur, B. A., Goodman, S., & Bell, M. M. (2015). Don’t touch the gadget because it’s hot! Mothers’ and children’s behavior in the presence of a contrived hazard at home: Implications for supervising children. Journal of Pediatric Psychology, 40 1, 85–95. Mueller, S., Remaud, H., & Chabin, Y. (2011). How strong and generalisable is the Generation Y effect? A cross‐cultural study for wine. International Journal of Wine Business Research, 23(2), 125–144. https://doi.org/10.1108/17511061111142990 NAEYC. (2012). Technology and interactive media as tools in early childhood programs serving children from birth through age 8. National Institute for Educational Policy Research. (2014). Zenkoku Gakuryoku Gakusyu Jyokyo Cyosa [Japanese]. Nielsen Company. (2009). Television, Internet, and mobile usage in the U.S.: A2/M2 Three Screen Report. Nielsen Company. Nielsen, M. (2012). Imitation, pretend play, and childhood: Essential elements in the evolution of human culture? Journal of Comparative Psychology, 126(2), 170–181. https://doi.org/10.1037/a0025168 Novianti, R., Febrialismanto, F., Puspitasari, E., & Hukmi, H. (2020). Meningkatkan pengetahuan orang tua dalam mendidik anak di era digital di Kecamatan Koto Gasib Kabupaten Siak Provinsi Riau [Increasing parental knowledge in educating children in the digital era in Koto Gasib Sub-district, Siak Regency, Riau Province]. Riau Journal of Empowerment, 3(3), 183–190. https://doi.org/10.31258/raje.3.3.183-190 Novianti, R., & Garzia, M. (2020). Penggunaan Gadget pada Anak; Tantangan Baru Orang Tua Milenial[Use of Gadgets in Children; Millennial Parents' New Challenge]. Jurnal Obsesi: Jurnal Pendidikan Anak Usia Dini, 4(2), 1000–1010. Pediatrics, A. A. O. (2016). American Academy of Paediatrics announces new recommendations for children’s media use. Advocacy & Policy. Radesky, J. S., & Christakis, D. A. (2016). Increased Screen Time: Implications for Early Childhood Development and Behaviour. Paediatric Clinics of North America, 63(5), 827–839. https://doi.org/10.1016/j.pcl.2016.06.006 Ransdell, S., Kent, B., Gaillard-Kenney, S., & Long, J. (2011). Digital immigrants fare better than digital natives due to social reliance: Digital immigrants and social reliance. British Journal of Educational Technology, 42(6), 931–938. https://doi.org/10.1111/j.1467-8535.2010.01137.x Rideout, V., &. Robb, M. B., & Robb, M. B. (2020). The commonsense census: Media use by kids aged zero to eight. Common Sense Media. Scott, F. L. (2021). Family mediation of preschool children’s digital media practices at home. Learning, Media, and Technology, 1–16. https://doi.org/10.1080/17439884.2021.1960859 Setianingsih, S. (2018). Dampak penggunaan gadget pada anak usia prasekolah dapat meningkatan resiko gangguan pemusatan perhatian dan hiperaktivitas [The impact of using gadgets on preschool-aged children can increase the risk of attention deficit disorder and hyperactivity]. Gaster, 16(2), 191–205. Sharkins, K. A., Newton, A. B., Albaiz, N. E. A., & Ernest, J. M. (2016). Preschool Children’s Exposure to Media, Technology, and Screen Time: Perspectives of Caregivers from Three Early Childcare Settings. Early Childhood Education Journal, 44(5), 437–444. https://doi.org/10.1007/s10643-015-0732-3 Sheedy, A. J., Brent, J., Dally, K., Ray, K., & Lane, A. E. (2021). Handwriting Readiness among Digital Native Kindergarten Students. Physical & Occupational Therapy In Pediatrics, 41(6), 655–669. https://doi.org/10.1080/01942638.2021.1912247 Steiner-Adair, C., & Barker, T. H. (2013). The Big Disconnect (1st ed.). Harper Collins. Strasburger, V. C., Jordan, A. B., & Donnerstein, E. (2010). Health effects of media on children and adolescents. Pediatrics, 125(4), 756–767. Sugiyono. (2017a). Statistika untuk Penelitian[Statistics for Research]. Alfabeta. Sugiyono, P. (2017b). Metode Penelitian Pendidikan: Pendekatan Kuantitatif, Kualitatif, R&D [Educational Research Methods: Quantitative, Qualitative, R&D Approach]. Cetakan Ke-25. Bandung: CV Alfabeta. Suhana, M. (2018). Influence of Gadget Usage on Children’s Social-Emotional Development. 169(Icece 2017), 224–227. https://doi.org/10.2991/icece-17.2018.58 Sylva, K. (1994). School Influences on Children’s Development. Journal of Child Psychology and Psychiatry, 35(1), 135–170. https://doi.org/10.1111/j.1469-7610.1994.tb01135.x Takeuchi, H., Taki, Y., Hashizume, H., Asano, K., Asano, M., Sassa, Y., Yokota, S., Kotozaki, Y., Nouchi, R., & Kawashima, R. (2016). Impact of videogame play on the brain’s microstructural properties: Cross-sectional and longitudinal analyses. Molecular Psychiatry, 21(12), 1781–1789. Test, J. E., Cunningham, D. D., & Lee, A. C. (2010). Talking With Young Children: How Teachers Encourage Learning. Dimensions of Early Childhood, 38(3), 3–14. Tootell, H., Freeman, M., & Freeman, A. (2014). Generation Alpha at the Intersection of Technology, Play and Motivation. 2014 47th Hawaii International Conference on System Sciences, 82–90. https://doi.org/10.1109/HICSS.2014.19 Twenge, J. M. (2017). IGen: Why today’s super-connected kids are growing up less rebellious, more tolerant, less happy—And completely unprepared for adulthood—And what that means for the rest of us. Simon and Schuster. UNESCO. (2014). Information and Communication Technology (ICT) In Education in Asia. Information Papers, 6(22), 6. UNICEF. (2017). UNICEF for Every Child. The State of The World’s Children 2017. Children in a Digital World. Valkenburg, P. M., Peter, J., & Schouten, A. P. (2006). Friend Networking Sites and Their Relationship to Adolescents’ Well-Being and Social Self-Esteem. CyberPsychology & Behavior, 9(5), 584–590. ht